Cardiac function and extracellular matrix morphology are altered by chronic high fat diet in Drosophila larvae - Rachel M. Andrews; Saumya Naik; Katie Pelletier; J. Roger Jacobs (PLoS ONE, 2025)
Cardiovascular disease is characterized by aberrant and excessive extracellular matrix (ECM) remodelling, termed fibrosis. Fibrotic remodelling is typically triggered by inflammation, which occurs systemically in obesity. Despite the contribution of fibrosis to adverse clinical outcomes and disease progression, there are no available treatments for this condition. Developing therapeutics for chronic conditions requires an understanding of in vivo ECM regulation, and how the ECM responds to a systemic challenge. We have therefore developed a Drosophila model for obesity via chronic high fat diet feeding of larvae and evaluated the response of the cardiac ECM to this metabolic challenge. We found that this model displays a striking reorganisation of the cardiac ECM, with fibres oriented anterior to posterior, rather than in a complex network, suggesting tension modulation is altered. We also observe corresponding deficits in heart function, with high fat diet treatments resulting in an inability to contract the heart effectively at systole. Our study reveals that different genotypes tolerate different levels of dietary fat, and that some genotypes may require a different dietary supplementation regime to generate a cardiac phenotype. In summary, the Drosophila model for chronic high fat diet recapitulates many of the defects observed in human cardiovascular disease, allowing further evaluation of genetic and environmental influences on cardiac structure and physiology in disease states.